XML na ciência da informação: uma análise do MARC21 - Siqueira, Marcos Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
In the cataloguing process, indispensable for the Science of the Information appears the creation of forms of descriptive documentary representation, for that, its relation with the theories in representation ways studied by the Cognitive Science. That relation is the object of study of this research, that it will be ruled in the analysis of the format of exchange of bibliographical data Machine Readable Cataloging, MARC 21, in its version in Extensible Markup Language, XML, demarcation language that proves mechanisms of communication of data developed by the Science of the Computation, characterizing the theoretical referencial of the research starting from the existent interdisciplinary. The objective of the research is to detach the importance of XML for the Science of the Information, starting from the own structure of the language and of studies on Forms of Representation, introducing the version MARC 21 in XML as appropriate tool for documentary representation. The proposition presents theoretical and methodological subsidies that it detaches MARC 21 in its version XML as a relevant option of documentary representation, and it promotes a discussion about the need of development of software tools and not of new representation methods. Technical evidences about MARC 21 XML and the indication of the version MARC 21 in XML as appropriate method for documentary representation will base the proposition. Starting from an analysis methodology, it was verified that the need of development of methods and theories for the grounding of the documentary representation and also of effective implementation of software tools worried with the usability of the interface for optimization of the representation process, they cause difficulties in the presentation of a good cataloguing, especially, in what refers to the representation, description and exchange... (Complete abstract, click electronic address below)

No processo de catalogação, indispensável para a Ciência da Informação, ocorre a criação de formas de representação documentária descritiva, por isso, sua relação com as teorias de formas de representação estudadas pela Ciência Cognitiva. Essa relação é objeto de estudo dessa pesquisa, que se pautará na análise do formato de intercâmbio de dados bibliográficos Machine Readable Cataloging, MARC 21, em sua versão em Extensible Markup Language, XML, linguagem de marcação que prove mecanismos de comunicação de dados desenvolvida pela Ciência da Computação, caracterizando o referencial teórico da pesquisa a partir da interdisciplinaridade existente. O objetivo da pesquisa é destacar a importância da XML para a Ciência da Informação, a partir da própria estrutura da linguagem e de estudos sobre Formas de Representação, apresentando a versão MARC 21 em XML como ferramenta adequada para representação documentária. A proposição apresenta subsídios teóricos e metodológicos que destaca o MARC 21 em sua versão XML como uma relevante opção de representação documentária, e promove uma discussão sobre a necessidade de desenvolvimento de ferramentas de software e não de novos métodos de representação. Evidências técnicas sobre o MARC 21, XML e a indicação a versão MARC 21 em XML como método adequado para representação documentária embasarão a proposição. A partir de uma metodologia de análise, verificou-se que a necessidade de desenvolvimento de métodos e teorias para a fundamentação da representação documentária e também de implementação efetiva de ferramentas de software preocupada com a usabilidade da interface para otimização do processo de representação, ocasionam dificuldades na apresentação de uma catalogação de qualidade, especialmente, no que se refere a representação...
Keywords: XML (Linguagem de marcação de documento); Catalogação - Processamento de dados; Formatos MARC; MARC21; Metadados; Decimal Classification; Juridical Documentation; Working Resource